Arte y Gelassenheit. Estética, ética y lógica originarias en el pensar de Heidegger - Gutiérrez Pozo, Antonio (Logos. Anales del Seminario de Metafísica, 2003)
Separating from the humanistic/metaphysical interpretation, Heidegger’s original view of Aesthetics, Ethics and Logic, contains a new humanism centred in the idea of Gelassenheit. But Gelassenheit, the nucleus of poetic dwelling of man, is also the essence of the original artistic experience, that is in fact a poetic of the receptivity of being, in other words, an ethical and ontological original experience.